Ensuring railway safety on a national scale: national and international experience - A. A. Bychkova (Вестник университета)
The article considers the main measures to create safety conditions in railway transport in foreign countries and compares them with the methods of safety provision by the domestic carrier JSC “Russian Railways”. It is noted that today Russia has its own practices for maintaining a level of security, but that alternative foreign approaches would improve the level of protection. The author analyses accident data and proposes additional measures to reduce the number of accidents. Scenario modelling and the integrated situation analysis method have been proposed as a method for selecting measures to ensure safety and improve the situation in the railway transport sector.